Pengaruh Heat Exchanger pada Pipa Ganda dengan Variasi Jumlah dan Jarak Sirip - Selviyanty, Veny; Abu, Risal (Universitas Pahlawan Tuanku Tambusai, 2024)
Heat exchangers are widely used in various industries because they have several advantages, heat exchangers have an overall heat transfer coefficient so they are able to transfer heat and have a low pressure drop (∆P), the problem is to reduce the pressure drop but have a high heat transfer coefficient which is very difficult. This research tries to provide a solution by adding Delta Wing shaped fins, with materials namely aluminum, copper, stainless steel and varying the distance and number of fins on the inner pipe (tube) to produce a heat exchanger that has a high heat transfer coefficient and has a pressure drop. the low one. The results showed that the variation in delta wing fin spacing in aluminum was 6.55%, copper 6.4% and stainless steel 11.61%, variation in the number of delta wing fins in aluminum 18.36%, copper 17.98%, stainless steel 20, 18% means that the effect of varying the distance and number of fins on the tube surface can increase the heat transfer coefficient with an increase of 3% for variations of 4/10 to 4/20 and increase the pressure drop.